Correlation between phenotypic virulence traits and antibiotic resistance in Pseudomonas aeruginosa clinical isolates. (January 2022) - Nassar, Osama; Desouky, Said E.; El-Sherbiny, Gamal M.; Abu-Elghait, Mohammed
Abstract: Pseudomonas aeruginosa is a ubiquitous pathogen capable of infecting virtually all tissues and its one of the standout amongst the most hazardous microorganisms of high morbidity and mortality rates especially in debilitated patients with few successful antibiotic choices available. This pathogen regulating most virulence traits by that so-called quorum sensing (QS), a cell to cell communication system. the present study was intended to phenotypically evaluate the activity of specific virulence traits (including swarming and swimming motility, protease, pyocyanin, and biofilm production) in Pseudomonas aeruginosa clinical isolates and assess the statistical correlation between these traits and antibiotic resistance. One hundred and thirteen bacterial isolates were obtained from different clinical samples and identified as P. aeruginosa, among them, 73.4% have the ability to forming biofilm with different degrees; 59.2% were able to produce pyocyanin pigment while all isolates having the ability to make swarming and swimming motility and able to produce protease enzyme with different degrees. The isolates that produce the higher levels of the virulence traits were identified by both biochemical using Vitek2 automated system and genetically via 16s rRNA gene analysis. The statistical analysis results indicate that a positive significant correlation was found between biofilm formation and other studied virulence traits except for protease (r = 0.584: 0.324, P < 0.05) while a non-significant correlation was found between biofilm formation and protease activity (r = 0.105, P ˃ 0.05). Swimming and swarming motility have a positive significant correlation with other studied virulence traits (r = 0.613: 0.297, P < 0.05) except for protease. Pyocyanin pigment production have a positive significant correlation with other studied virulence traits (r = 0.33: 0.297, P < 0.05) except for protease. on the other hand, negative significant correlations were found between biofilm formation, swimming; and swarming motility, Pyocyanin pigment production, and the susceptibility of antibiotics (r = −0.512: −0.281, P < 0.05). Detection of such correlations in P. aeruginosa is useful for study the behavior of this pathogen and may be provide a new target for the treatment of MDR infections. Graphical abstract: Image 1 Highlights: Negative correlations were found between diverse virulence traits of P. aeruginos a and the antibiotic susceptibility pattern. The biofilm-forming ability was significantly higher among MDR pseudomonas aeruginosa isolates. The statistical analysis exhibited no correlation seems to be between protease activity and the production of other virulence traits nor with antibiotic susceptibility in pseudomonas aeruginosa .